Analysis of Heavy Metal Pollution in the Water of the Halda River: A Distinctive Breeding Habitat for Carp Fish in Bangladesh - Afsana Kamal; Md. Manzoorul Kibria; Shahadat Hossain; Chowdhury Kaiser Mahmud; Rashmi Roy; Nighat Sultana Resma (Veterinary Medicine and Science)
ABSTRACT Background The present study aimed to assess the heavy metal concentrations in water from different sampling sites of the Halda River, the only natural breeding ground of Indian major carps. Objectives We have analysed the contamination level and seasonal variations of heavy metals (viz. Fe, Cu, Zn, Cr, Cd and Pb). The favourability of the breeding environment was assessed by different contamination indices. Methods Samples were collected from six sampling sites for four different seasons, and the metal concentrations were determined for water samples using Flame atomic absorption spectrophotometer. Results The obtained order of mean concentrations of heavy metals for four seasons was winter > spring > monsoon > pre‐monsoon, and the assessed mean concentrations (mg/L) of heavy metals follow the trend: Fe (9.129) > Pb (0.033) > Zn (0.024) > Cr (0.017) > Cu (0.012) > Cd (0.002). The concentration of Fe was found above the permissible limit set by the World Health Organization (WHO) (Guidelines for Water Quality) and ECR (1997), and the concentrations for Pb were found above the USEPA (2006) limit in all four seasons. Contamination indices (heavy metal pollution Index [HPI] and metal index [MI]) indicate that during winter and monsoon, the river water metal condition is critical (HPI > 100) and the sites are moderately as well as slightly (1< MI <2) affected by the studied heavy metals. Contamination indices, such as contamination factors (Cf), degree of contamination (Cdeg) and the pollution load index (PLI), demonstrate the fact that Fe and Pb remarkably contaminated the studied sampling sites. The Pearson correlation matrix and the principal component analysis (PCA) revealed that the studied metals are connected by their sources, which can be geological or anthropogenic. Conclusion Urgent initiatives need to be taken, and effective strategies must be implemented to control the different sources responsible for the entry of heavy metals into the Halda River water.